Arguments in behalf of the United States, with supplement and appendix [electronic resource] : presented to the commissioners under the treaty between Great Britain and the between Great Britain and the United States for the final settlement of theclaims of the Hudson's Bay and Puget's Sound Agricultural Companies - Cushing, Caleb, 1800-1879.; British and American Joint Commission for the Final Settlement of the Claims of the Hudson's Bay and Puget's Sound Agricultural Companies. ([Washington? : s.n.], 1868)
No supplements or appendix are included in this edition. Discontinuous paging: "Memorial of the Hudson's Bay Company", " Memorial of the Puget's Sound Agricultural Company", and "Motion to Amend Memorial"--p. [3]-24. "Claims of the Hudson's Bay Company," signed C. Cushing--p. [1]-156. Electronic reproduction. Mode of access: Internet. 44